Activating collective co-production of public services: influencing citizens to participate in complex governance mechanisms in the UK. (March 2016) - Bovaird, Tony; Stoker, Gerry; Jones, Tricia; Loeffler, Elke; Pinilla Roncancio, Monica
Previous research has suggested that citizen co-production of public services is more likely when the actions involved are easy and can be carried out individually rather than in groups. This article explores whether this holds in local areas of England and Wales. It asks which people are most likely to engage in individual and collective co-production and how people can be influenced to extend their co-production efforts by participating in more collective activities. Data were collected in five areas, using citizen panels organized by local authorities. The findings demonstrate that individual and collective co-production have rather different characteristics and correlates and highlight the importance of distinguishing between them for policy purposes. In particular, collective co-production is likely to be high in relation to any given issue when citizens have a strong sense that people can make a difference ('political self-efficacy'). 'Nudges' to encourage increased co-production had only a weak effect. Points for practitioners: Much of the potential pay-off from co-production is likely to arise from group-based activities, so activating citizens to move from individual to collective co-production may be an important issue for policy. This article shows that there is major scope for activating more collective co-production, since the level of collective co-production in which people engage is not strongly predicted by their background and can be influenced by public policy variables. 'Nudges' may help to encourage more collective co-production but they may need to be quite strong to succeed.